2016
DOI: 10.1016/j.molcel.2016.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cell-Autonomous Regulation of Prostate Epithelial Homeostasis by Androgen Receptor

Abstract: Summary Prostate inflammation has been suggested as an etiology for benign prostatic hyperplasia (BPH). We show that decreased expression of the androgen receptor (AR) in luminal cells of human BPH specimens correlates with a higher degree of regional prostatic inflammation. However, the cause-and-effect relationship between the two events remains unclear. We investigated specifically whether attenuating AR activity in prostate luminal cells induces inflammation. Disrupting luminal cell AR signaling in mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 40 publications
5
86
0
Order By: Relevance
“…Cell type-specific changes are lost with this approach. As an example of how our group is attempting to deal with cellular heterogeneity, we recently showed that AR expression is decreased with increasing prostate volume, but only in isolated luminal epithelia (103). Stromal AR slightly increased with prostate volume, which is why AR looked unchanged in our previous whole tissue molecular signature.…”
Section: Cells Of Origin For Distinct Bph Phenotypesmentioning
confidence: 99%
“…Cell type-specific changes are lost with this approach. As an example of how our group is attempting to deal with cellular heterogeneity, we recently showed that AR expression is decreased with increasing prostate volume, but only in isolated luminal epithelia (103). Stromal AR slightly increased with prostate volume, which is why AR looked unchanged in our previous whole tissue molecular signature.…”
Section: Cells Of Origin For Distinct Bph Phenotypesmentioning
confidence: 99%
“…We and others have shown that IL-1β and the other major IL-1 family member, IL-1 alpha (IL-1α), can repress androgen receptor (AR) accumulation and activity. [4][5][6][7] AR is a nuclear receptor transcription factor. 8 AR and its hormone ligand, androgen, are required for prostate cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…The conditional ablation of AR in prostate luminal epithelial cells results in decreased levels of CLDN3, CLDN4, and CLDN8 and widened intercellular spaces at the level of the tight junction. In addition, AR ChIP‐seq in adult male mice confirmed binding to the promoter regions of the genes encoding these proteins . Combined, these observations suggest that AR directly regulates the levels of junctional genes in the prostate epithelium.…”
Section: Nuclear Receptors Superfamilymentioning
confidence: 73%
“…Combined, these observations suggest that AR directly regulates the levels of junctional genes in the prostate epithelium. Since impaired tight junction integrity in the prostate epithelium is believed to be an underlying cause of age‐associated prostate diseases, such as prostate cancer and benign prostatic hypertrophy, it will be interesting to determine whether testosterone treatment in aging men can effectively increase the expression of junctional components to reestablish tight junction integrity.…”
Section: Nuclear Receptors Superfamilymentioning
confidence: 99%